2002
DOI: 10.1603/0022-2585-39.1.221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Temperature on the Ability ofCulex pipiens(Diptera: Culicidae) to Transmit West Nile Virus

Abstract: Environmental temperature can affect the ability of mosquitoes to transmit an arbovirus. However, results of various studies indicate that these effects are not consistent among viruses or mosquito species, and there is no information available on the effect of environmental temperature on the ability of North American mosquito species to transmit West Nile (WN) virus. We evaluated the effect of incubation temperature (18, 20, 26, or 30 degrees C) on the ability of Culex pipiens L. derived from specimens colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
211
2
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(227 citation statements)
references
References 23 publications
8
211
2
6
Order By: Relevance
“…Holding mosquitoes for longer periods of time increased dissemination, and thus transmission rates for Cx. pipiens (Dohm et al 2002). Therefore, studies may need to be conducted that evaluate mosquitoes after a longer period of extrinsic incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holding mosquitoes for longer periods of time increased dissemination, and thus transmission rates for Cx. pipiens (Dohm et al 2002). Therefore, studies may need to be conducted that evaluate mosquitoes after a longer period of extrinsic incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studies may need to be conducted that evaluate mosquitoes after a longer period of extrinsic incubation. Likewise, environmental temperatures are known to inßuence vector competence for arboviruses in general, and WNV in particular (Jupp 1974, Cornel et al 1993, Dohm et al 2002. Therefore, additional studies are needed to determine the impact of environmental temperature on the ability of North American mosquitoes to transmit WNV.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was shown that the replication cycle is completed more quickly in mosquitoes at higher temperatures [38,39], while a clear association was found between extreme heat and outbreak intensity in humans [4,18,22,35,[40][41][42][43]. At the same time, it is important to note that, in some cases, extremely high temperatures begin to slow down mosquito activity.…”
Section: (A) Temperaturementioning
confidence: 99%
“…Ornithophagic species within the genus Culex are important vectors and responsible for zoonotic WNV transmission among birds (Molaei et al 2006). Culex in California are quiescent or diapause during cold winter months (Nelms et al 2013a,b), and low temperatures hinder WNV replication within the overwintering mosquito hosts (Dohm et al 2002, Reisen et al 2006b). Nevertheless, researchers in New York State documented American Crow (Corvus brachyrhynchos; hereafter "crow") mortality during February and March of 2005 (Dawson et al 2007).…”
mentioning
confidence: 99%